Bank Indonesia Policy In Critical Settlement of National Banking - Surti Yustianti; Syamsul Komar (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2017)
This study aims to determine responsibility for the measures taken by Bank Indonesia in accordance with its authority and position assigned to Bank Indonesia officials. Policy made by Bank Indonesia can be right or wrong with the principles of prudence and in good faith. Bank Indonesia officials have authority related to their positions. If there is an element of bad faith and lack of prudence in their authority that results in financial losses of the state, these policies can be categorized as a crime in the banking sector. If a Bank Indonesia official made a mistake in implementing the policy, he holds authority and personal responsibility.